Chemical treatments and tensile properties of sugarcane bagasse rind filled poly (vinyl chloride) - Wirawan, Riza; Salit, Mohd Sapuan; Yunus, Robiah; Abdan, Khalina (2009)
This study examined influence of different treatments, including fibre treatment with benzoic acid or sodium hydroxide as well as the incorporation of Poly[methylene(polyphenyl) isocyanate] (PMPPIC) as coupling agent. The tensile properties were examined for treated and untreated sugarcane bagasse rind filled unplasticised poly (vinyl chloride) composites. Chemical treatments were found to be effective in improving the tensile strength and modulus of the composite when washed fibre was used. The tensile strength, however, is lower compared to that of untreated sugarcane bagasse rind filled composite when unwashed fibre was used. It is suspected that sucrose may give contribution to the fibre-matrix interfacial adhesion.